2019
DOI: 10.3897/zookeys.885.34638
|View full text |Cite
|
Sign up to set email alerts
|

Thitarodes shambalaensis sp. nov. (Lepidoptera, Hepialidae): a new host of the caterpillar fungus Ophiocordyceps sinensis supported by genome-wide SNP data

Abstract: A new species of ghost moth, Thitarodes shambalaensissp. nov., is described from Yanzigou glacier, Mt. Gongga, Sichuan, China. The species is a host of the economically important caterpillar fungus Ophiocordyceps sinensis. Establishment of this new species is supported by morphology and genetic differentiation measured in a CO1 phylogeny and in genome-wide SNP coverage. A summary tree from 538 sequences of different genetic markers from Thitarodes (including sequences extracted from caterpillar fungus scleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…and T. damxungensis [21]. Based on the phylogenetic tree constructed by 13 PCGs from the previously described genomes, GG♂× GG♀ was identified as T. shambalenensis, and SD♂× SD♀ was considered to be an undescribed Thitarodes species (Figure 5), given the reasonable threshold for inter-species variation (2.5% genetic distance) [43,64]. Interestingly, SD♂× GG♀ was close to GG♂× GG♀, according to the genetical similarities, which confirms the maternal inheritance of mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…and T. damxungensis [21]. Based on the phylogenetic tree constructed by 13 PCGs from the previously described genomes, GG♂× GG♀ was identified as T. shambalenensis, and SD♂× SD♀ was considered to be an undescribed Thitarodes species (Figure 5), given the reasonable threshold for inter-species variation (2.5% genetic distance) [43,64]. Interestingly, SD♂× GG♀ was close to GG♂× GG♀, according to the genetical similarities, which confirms the maternal inheritance of mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 66%
“…T. shambalaensis (GG♂× GG♀) identified by morphology (male genitalia) and genetic cox1 phylogeny [43] and an undescribed Thitarodes species (SD♂× SD♀) live in different locations in the Tibetan Plateau. In the present study, interspecific hybridization between these two distinct ghost moth species was demonstrated in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations